2022
DOI: 10.1021/acsomega.2c02206
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivation of 3D Cell-Imprinted Polydimethylsiloxane Surfaces by Bone Protein Nanocoating for Bone Tissue Engineering

Abstract: Physical and chemical parameters that mimic the physiological niche of the human body have an influence on stem cell fate by creating directional signals to cells. Micro/nano cell-patterned polydimethylsiloxane (PDMS) substrates, due to their ability to mimic the physiological niche, have been widely used in surface modification. Integration of other factors such as the biochemical coating on the surface can achieve more similar microenvironmental conditions and promote stem cell differentiation to the target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 67 publications
2
7
0
Order By: Relevance
“…After O 2 plasma treatment, the PDMS surface was successively functionalized with APTES and GA. 51 Finally, MEL was immobilized on the GA−PDMS surface through imine formation between the amine groups of MEL and the aldehyde groups of GA. As shown in Figure S4, the FT-IR spectrum of the MEL-immobilized PDMS surface showed C�N stretching and N−H bending vibration peaks at 1653 and 1530 cm −1 , respectively. 54,55 Thus, this spectrum indicated that MEL molecules used as templates for molecular imprinting were successfully immobilized on the GA−PDMS surface. For the formation of the S-MIP film, after the MIP precursor solution was dropped on QC substrates, microcontact printing was performed using the MEL-immobilized PDMS mold to photochemically crosslink CB-PI.…”
mentioning
confidence: 86%
“…After O 2 plasma treatment, the PDMS surface was successively functionalized with APTES and GA. 51 Finally, MEL was immobilized on the GA−PDMS surface through imine formation between the amine groups of MEL and the aldehyde groups of GA. As shown in Figure S4, the FT-IR spectrum of the MEL-immobilized PDMS surface showed C�N stretching and N−H bending vibration peaks at 1653 and 1530 cm −1 , respectively. 54,55 Thus, this spectrum indicated that MEL molecules used as templates for molecular imprinting were successfully immobilized on the GA−PDMS surface. For the formation of the S-MIP film, after the MIP precursor solution was dropped on QC substrates, microcontact printing was performed using the MEL-immobilized PDMS mold to photochemically crosslink CB-PI.…”
mentioning
confidence: 86%
“…Babaei et al, showed improvement in cell adhesion, proliferation and osteogenic differentiation by coating the osteoblast imprinted substrates with bone extracted proteins. 164 In another recently published report, it was found that small molecules such as β-carotene can enhance the differentiation capacity of cell imprinting. 216 …”
Section: Cells Cultured On Imprinted Substratesmentioning
confidence: 98%
“… 115 The results of previous studies indicate that PDMS, at a 1:10 ratio of curing agent, induces more osteogenicity in stem cells than polystyrene plates. 163 , 164 In some studies, engineering approaches such as lithography have been used to generate substrates with 3D features that mimic physiological shapes and patterns similar to native tissues. For example, aligned microgrooves are fabricated by photolithography to resemble the physiological dimensions of the ECM structure in tendons, muscles, nervous and cartilage tissues.…”
Section: Cells Cultured On Imprinted Substratesmentioning
confidence: 99%
“…Keyhanvar et al and Mashinchian et al obtained comparable results using keratinocytes [ 139 , 140 ]. Babaei et al demonstrated this effect for osteoblast-imprinted PDMS [ 141 ]. In this study, the effect was further enhanced by chemical modification with bone lysate.…”
Section: Influence Of Materials Properties On Adipose-derived Stem Ce...mentioning
confidence: 99%